(untitled) (Proceedings of the International Conference on Gender and Sexuality, 2025)
Research continues to identify a myriad of negative consequences ranging from name calling, cyberbullying, to gang-rape for gay or lesbian students at the institutions of higher learning. However, this study determined the elements associated with self-acceptance and resilience amongst gay and lesbian students from one South African university, based in a rural setting. Carol Ryff’s psychological dimensions theory and Michael Ungar’s resilience theory guided a qualitative study of six lesbians and six gay students, aged 18 -28, purposively selected from five faculties. The participants gave their informed consent to be audio-taped during face-to face interviews and were later debriefed by one of the researchers, a qualified clinical psychologist. To ensure trustworthiness, Lincoln and Guba’s principles were opted for, namely, credibility, dependability, transferability, and confirmability. Tesch’s steps of thematic analysis were useful in identifying the following themes: self-esteem, purpose in life, spiritual resilience, sense of belonging, support from the lecturers and family members, gym and sport, discrimination, and drug and alcohol abuse. Better coping strategies for gay and lesbian students require a multi-dimensional approach from the university management, family members, and the implementation of policies that promote tolerance, sexual health, and respect for gay rights. It would be proper to determine how the gay and lesbian students’ family and their sexual partners influence their university experiences.